2015
DOI: 10.3382/ps/pev087
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between supplemented mineral phosphorus and phytase on phytate hydrolysis and inositol phosphates in the small intestine of broilers ,

Abstract: Phytate breakdown in the digestive tract of broilers is affected by supplements of mineral phosphorus (P) and phytase with unknown interactions between the 2 factors. It was the objective to study phytate hydrolysis and the presence of inositol phosphate isomers (InsPs) as affected by supplements of mineral P and phytase in the small intestine of broilers. Fifteen-day old broilers were assigned to 48 pens of 20 broilers each (n = 8 pens/treatment). Two low-P corn-soybean meal-based diets without (BD-; 4.4 g P/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
80
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 40 publications
14
80
1
1
Order By: Relevance
“…Besides determination of the enzymatic properties of a phytase, however, in vitro simulation is considered as a good complementary tool to preselect promising phytase candidates as a feed supplement. To compare the different enzyme products used in the study, the phytase activity needed to achieve a 50% reduction in IP 6 and a 50% release of the P i bound to the myo-inositol ring was estimated using nonlinear fit of a negative exponential model of the observed data (Table 3). According to the model, between 319 and 581 U phytase per kilogram of microwave-treated ground wheat was needed to achieve a 50% reduction in IP 6 , whereas between 952 and 2606 U phytase per kilogram of ground wheat was required to release 50% of the P i bound to the myo-inositol ring when the lower buffer volume was used.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Besides determination of the enzymatic properties of a phytase, however, in vitro simulation is considered as a good complementary tool to preselect promising phytase candidates as a feed supplement. To compare the different enzyme products used in the study, the phytase activity needed to achieve a 50% reduction in IP 6 and a 50% release of the P i bound to the myo-inositol ring was estimated using nonlinear fit of a negative exponential model of the observed data (Table 3). According to the model, between 319 and 581 U phytase per kilogram of microwave-treated ground wheat was needed to achieve a 50% reduction in IP 6 , whereas between 952 and 2606 U phytase per kilogram of ground wheat was required to release 50% of the P i bound to the myo-inositol ring when the lower buffer volume was used.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…P is, however, a non-renewable resource that is expected to be depleted in the next 100 years (Shastak and Rodehutscord, 2013). Phytate, an organic source of P contained in plant seeds and plant-based diets for broilers, is a principal source of P for the animal, but it has the disadvantage of not being easily accessible by broilers (Witzig et al, 2015; Zeller et al, 2015). The P availability of plant-based diets can be improved by supplementing the diets with phytase, an enzyme that increases P digestibility and reduces P excretion (Witzig et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al (2013) used an even lower NPP level (1.0 g/kg, total phosphorus 3.4 g/kg) than in this study, and they also reported a higher coefficient of apparent ileal digestibility of phosphorus from this diet (0.506) compared with phosphorus digestibility from diet with total phosphorus 5.7 g/kg and 3.2 NPP g/kg (0.474). Thus, it can be inferred that the digestibility of phytate phosphorus in Zeller et al (2015) and Shastak et al (2014) who published that mineral phosphorus supplementation reduces the degradation of myoinositol phosphates. On the other hand, Hafeez et al (2016) also published very similar coefficients of apparent ileal phosphorus digestibility in layer diets (from 0.311 to 0.409).…”
Section: Discussionmentioning
confidence: 99%